Fate of Viable but Non-culturable Listeria monocytogenes in Pig Manure Microcosms - Desneux, Jérémy; Biscuit, Audrey; Picard, Sylvie; Pourcher, Anne-Marie (Frontiers in Microbiology, 2016)
The fate of two strains of L. monocytogenes and their ability to become viable but non-culturable (VBNC) was investigated in microcosms containing piggery effluents (two raw manures and two biologically treated manures) stored for two months at 8°C and 20°C. Levels of L. monocytogenes were estimated using the culture method, qPCR, and propidium monoazide treatment combined with qPCR (qPCRPMA). The chemical composition and the microbial community structure of the manures were also analysed. The strains showed similar decline rates and persisted up to 63 days. At day zero, the percentage of VBNC cells among viable cells was higher in raw manures (81.5-94.8%) than in treated manures (67.8-79.2%). The changes in their proportion over time depended on the temperature and on the type of effluent: the biggest increase was observed in treated manures at 20°C and the smallest increase in raw manures at 8°C. The chemical parameters had no influence on the behaviour of the strains, but decrease of the persistence of viable cells was associated with an increase in the microbial richness of the manures. This study demonstrated that storing manure altered the culturability of L. monocytogenes, which rapidly entered the VBNC state, and underlines the importance of including VBNC cells when estimating the persistence of the pathogens in farm effluents.